2023
DOI: 10.1002/mds.29645
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Nicotinamide Riboside Use Improves Coordination and Eye Movements in Ataxia Telangiectasia

Rebecca Presterud,
Wei Hai Deng,
Anna Berit Wennerström
et al.

Abstract: BackgroundSupplementation of nicotinamide riboside (NR) ameliorates neuropathology in animal models of ataxia telangiectasia (A‐T). In humans, short‐term NR supplementation showed benefits in neurological outcome.ObjectivesThe study aimed to investigate the safety and benefits of long‐term NR supplementation in individuals with A‐T.MethodsA single‐arm, open‐label clinical trial was performed in individuals with A‐T, receiving NR over a period of 2 years. Biomarkers and clinical examinations were used to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Recent clinical studies have demonstrated the benefits of NAD + supplementation to neurological conditions. NR supplementation has been shown to improve coordination and eye movement in patients with ataxia telangiectasia (Presterud et al., 2023 ), increase cerebral NAD + levels associated with altered brain metabolism and clinical improvement (Brakedal et al., 2022 ), and stimulate mitophagy which reverses memory impairment in nematodes, mice, and human cells (Fang, Hou, Palikaras, et al., 2019 ). These studies highlight the potential for NAD + supplementation as a therapeutic intervention and hint at the possibility for additional benefits from dual KP suppression and NAD + supplementation in the treatment of neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical studies have demonstrated the benefits of NAD + supplementation to neurological conditions. NR supplementation has been shown to improve coordination and eye movement in patients with ataxia telangiectasia (Presterud et al., 2023 ), increase cerebral NAD + levels associated with altered brain metabolism and clinical improvement (Brakedal et al., 2022 ), and stimulate mitophagy which reverses memory impairment in nematodes, mice, and human cells (Fang, Hou, Palikaras, et al., 2019 ). These studies highlight the potential for NAD + supplementation as a therapeutic intervention and hint at the possibility for additional benefits from dual KP suppression and NAD + supplementation in the treatment of neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Following the previous findings that hyper PARylation-induced depletion of NAD + is associated with accelerated aging in ATM -deficient C elegans and mouse models ( 23 ), her lab has conducted a 2-year clinical study on the effect of supplementation of an NAD + precursor NR in ataxia-telangiectasia (A-T) patients, a rare genetic disorder with premature aging features. She reported that NR improves neuro-motor function in A-T patients and may also delay disease progression when compared to historical control groups ( 24 ). These findings offer promise for potential clinical interventions for neurodegenerative diseases driven by DNA damage response and genomic instability.…”
Section: Hallmarks Of Aging: Mechanisms and Linkages To Aging And Dis...mentioning
confidence: 99%
“…Moreover, drugs to slow disease progression are currently being explored in clinical trials. Nicotinamide riboside and NAD supplementation is a promising candidate treatment, where supplementation has been associated with improved performance on neurological and motor tests [44].…”
Section: Atipeksenmentioning
confidence: 99%